Mapeamento geotécnico aplicado à seleção de áreas preferenciais para instalação de aterros sanitários e cemitérios na região metropolitana de Belém (PA) - SOARES, Ádria Kanome Mori (2019)
This paper uses geotechnical data to define preferred sites to sanitary landfills and cemeteries installation. Attributes of terrain physiography and soil use and occupation are analyzed; they interfere in the selection of the best location of such engineering works, aiming at minimizing financial costs, risks to the environment and public health. It is based on maps of Urban Area and Urban Expansion, Solid Ground and Lowland Areas, Institutional Areas and Environmental Protection Areas, Equipotentiometric of the Free Aquifer, Hydrographic Basins, Hydrographic Microbasins and Direction of the Wind. With data crossing and interpretation in GIS environment provided by ArcGIS 10.4 software, it was possible to elaborate two charts: Preferred Areas for the Installation of Sanitary Landfills in the Metropolitan Region of Belém (PA) Chart and Preferred Areas for the Installation of Cemeteries in the Metropolitan Region of Belém (PA) Chart, both being in a scale of 1:50,000.